Probiotic treatment in children with lactose intolerance – An open labeled the one group pre-test post-test experimental study - Zainul Arifin; Aswitha D. Boediarso; Taralan Tambunan (Paediatrica Indonesiana, 2006)
Background Lactose intolerance is the most common disorder ofintestinal carbohydrate digestion. Probiotic that contains the cor-rect strain in appropriate amount can be used as an alternativedietary for lactose intolerance patients.Objective This study was designed to describe the role of probioticin relieving lactose intolerance symptoms in children consumedfull-cream milk.Methods This study was a clinical trial. Inclusion criteria was chil-dren aged 12-14 years old, had a good nutrition and health status,with positive breath hydrogen test (BHT) result and lactose intoler-ance symptom(s), and their parents gave consent. Forty-two chil-dren were included. All subjects consumed one glass (200 ml) offull-cream milk twice a day for 21 days and recorded intolerancesymptoms. Probiotic was added from 8 th to 21 st day in their milk,and responses of treatment were evaluated by scoring system(based on borborigmic, flatulence, abdominal bloating, nausea andvomiting, abdominal pain, and diarrhea symptoms). At the end ofstudy they were undergone second BHT examination.Results There were decreasing mean score rates at 7 th day (pre)13.8 (SD 5.5) compared with 7.5 (SD 3.5) at 14 th day (after) andwas statistically significant (P<0.001). Mean score rate at 7 th day(pre) 13.8 (SD 5.5) compared with 21 st day (after) was 0.119 (SD0.55) and was statistically significant (P<0.001). At the end of study,only 2 subjects showed clinical signs of lactose intolerance. Thirty-six subjects had normal BHT result at 21 st day and was statisti-cally significant (P<0.001).Conclusion Two weeks administration of probiotic could relievelactose intolerance symptoms in children consumed full-cream milk